Saint Augustine - Remond-Dalyac, Emmanuelle; Alloing, Louis ([Quezon City] Adarna House, 2011)
Augustine lived over 1500 years ago, but he is still one of the great teachers about God. It took him many years to find God. When he became a Christian, Augustine had to change the way he lived, and that isn't easy. Following God's way turned out to be full of surprises!
This is the story of a man who changed the way he lived to become a great teacher about God.
"Originally published in Bayard Jeunesse/Grain de Soleil (1994)."
Published jointly with Bayard Assumption Media Foundation.
Keywords: Augustine -- Saint, Bishop of Hippo -- Juvenile literature; Christian saints -- Algeria -- Hippo (Extinct city) -- Biography; Saints